Informal Governance, Community Resilience, and the Making of Public Space - Masooma Mohib Shakir; Samia Sarfaraz (International "Journal of Academic Research for Humanities", 2026)
Public spaces in informally developed Global South settlements are frequently studied through a lens of deprivation and institutional neglect, yet research on community-managed public space in marginalized settlements remains limited. Actively used public spaces in such settlements offer critical insight into community-led spatial governance under minimal administrative control. This paper examines how community organization, cultural identity, historical attachment, informal governance, and spatial networks sustain the vibrancy and resilience of two community-led public spaces — Dreamhouse and Bambasa Street — in the oldest Baloch-majority neighbourhoods of Lyari, Karachi. Using a qualitative case study approach, the research draws on 30 semi-structured interviews, 2 focus groups, spatial mapping, and photographic documentation with space coordinators and community representatives. Findings identify historical rootedness, community networks, football and welfare organizations, informal norms, and shared cultural identity as key structuring forces sustaining these spaces and generating place identity in marginalized urban contexts. This demonstrates how community-led, self-organized governance constitutes a form of decolonial urbanism, challenging planning assumptions that treat informality as deficiency and formal recognition as a prerequisite for legitimate public space. The paper argues for greater recognition of such informal, community-led spatial practices within urban planning and public-space governance frameworks.